SIZE AND DENSITY OF NON-ERODIBLE AGGREGATES IN SEDIMENTS OF SELECTED GULLIES AT NORTHERN IRAQ - Khalid Hassan; Yousif H. Al-Nasser; Omer N. Abid-Alkader (Mesopotamia Journal of Agriculture, 2017)
The objective of this study was to determine the morphometric characteristics and sediment size distribution as affected by position witin the gullies at northern region of Iraq.  The plan area, maximum depression depth, maximum length L and severity index for each gully unit were measured. The size distribution of each gully unit was analyzed mechanically for major grain size fractions and were characterized statistically using various type of statistical measures (median size, sorting, and skewness). The results showed that the addition of finer/coarse materials in 1st and 2nd catchments was deposited under the prevailing low and high energy conditions respectively.  Moreover the ability of the surface soil to accept the accelerated erosion, in these catchments was related to the stability of aggregates to the shearing force of running water. On the basis of this assumption, we can be expected that, the soil loss in the 1st gully catchment was greater than compared to 2nd, and it seems  that the morphometric characteristics and sediment-grain size distribution alone would be insufficient for  predicting  soil loss from gullies.